Developing a narrative communication intervention in the context of HPV vaccination - Sara E. Fleszar-Pavlović; Linda D. Cameron (Elsevier, 2024)
Objective: We outline the development of a narrative intervention guided by the Common-Sense Model of Self-Regulation (CSM) to promote Human Papillomavirus (HPV) vaccination in a diverse college population. Methods: We adapted the Obesity-Related Behavioral Intervention Trials (ORBIT) model to guide the development, evaluation, and refinement of a CSM-guided narrative video. First, content experts developed a video script containing information on HPV, HPV vaccines, and HPV-related cancers. The script and video contents were evaluated and refined, in succession, utilizing the think-aloud method, open-ended questions, and a brief survey during one-on-one interviews with university students. Results: Script and video content analyses led to significant revisions that enhanced quality, informativeness, and relevance to the participants. We highlight the critical issues that were revealed and revised in the iterative process Conclusions: We developed and refined a CSM guided narrative video for diverse university students. This framework serves as a guide for developing health communication interventions for other populations and health behaviors. Innovation: This project is the first to apply the ORBIT framework to HPV vaccination and describe a process to develop, evaluate, and refine comparable CSM guided narrative interventions that are tailored to specific audiences.